Efektifitas ovaprim terhadap lama waktu pemijahan, daya tetas telur dan sintasan larva ikan lele dumbo, Clarias gariepinus - Sinjal, Hengky (Universitas Sam Ratulangi, 2014)
Abstract This study aimed to determine the effect of different doses of ovaprim on spawning time, egg hatchability, and survival of African catfish larvae (Clarias gariepinus). The research was done in the Central Local Fish Seed (BBI) Jayapura, Papua Province. Experimental design used was Randomized Complete Design. The study consisted of four treatments namely 0 ml, 0.3 ml, 0.6 ml and 0.9 ml ovaprim, each with three replications. Data collected were spawning time, egg hatchability, and survival rate of African catfish larvae. The number of containers used was as much as 12 buckets (for spawning, hatching, and observation of survival rate of larvae). The results showed that treatment with different doses of ovaprim hormones provided a significant influence on the latency time of spawning, egg hatchability and survival rate of larval. The dose of 0.3 ml ovaprim caould increase the latency time of spawning, egg hatchability and survival rate of African catfish larvae. The average latency time of hatching was 552 minutes, spawning and egg hatchability 84.16% and survival rate of living larvae was 85.76%. Keywords : African catfish, Ovaprim, spawning time, egg hatchability, survival rate